Investigations of the spring spawning fish populations in the Athabasca and Clearwater Rivers upstream from Fort McMurray: Volume 1 - McCart, P. J.; Tripp, D. B. (1979)
Fisheries investigations were undertaken in the spring of 1978 (28 April to 25 June) in the Athabasca and Clearwater rivers upstream of Fort McMurray. The major objectives of the studies were to determine what spring spawners utilized these sections of the Athabasca and Clearwater rivers; to locate and describe their spawning grounds; and to describe the timing of spawning, hatching, and emergence in relation to environmental factors such as water temperature, turbidity, dissolved oxygen concentrations, and stream flow. Large numbers of longnose suckers spawned during mid May in the Athabasca River from Fort McMurray upstream to the Cascade Rapids, the same area used by fall spawning lake whitefish. The major concentrations were located just below the Mountain and Cascade rapids. There was no evidence of major spawning concentrations of this species elsewhere in the present study area. Shortly after spawning, longnose suckers left the project study area and presumably returned to the Peace-Athabasca Delta. Northern pike and burbot spawning and rearing areas were identified in the Clearwater River upstream of its junction with the Christina River. There was little or no spawning by either species in the Clearwater River downstream of the Christina River or in the Athabasca River upstream of Fort McMurray. No major concentrations of spawning walleye were located. However, based on the distribution of young-of-the-year, it appears that at least some walleye spawned at various localities in the Athabasca River from the Mountain Rapids to as far upstream as the Grand Rapids. There is no evidence that walleye spawned in the Clearwater River within the AOSERP study area. Lake whitefish young-of-the-year probably emerged and moved downstream out of the present study area before spring breakup. Longnose sucker young-of-the-year emerged at the beginning of June followed by pike, walleye, and white sucker young-of-the year later in June. The Athabasca River, and to a lesser extent the Clearwater River, provide valuable ...